The spatial ecology of an endemic desert shrub - Gough, Lauren (2010)
Using spatial patterns to infer biotic and abiotic processes underlying plant population dynamics is an important technique in contemporary ecology, with particular utility when investigating and shrub population dynamics, for which experimental and observational methodologies are rarely feasible. Using a novel one-class classification technique, the locations of over 17,000 Spartocytisus supranubius individuals were mapped from aerial imagery generating a spatially extensive (162 ha), yet accurate, dataset.